Association of circulating muscle-derived myokines irisin and myostatin with COVID-19 severity - Daroszewski, Cyryl; Grzegrzółka, Jędrzej; Kosacka, Monika; Brzecka-Bonnaud, Anna (Frontiers in Endocrinology, 2026)
IntroductionSkeletal muscles secrete myokines, including irisin and myostatin, which regulate inflammation and metabolism and may influence the severity of SARS-CoV-2 infection. This study investigated the associations between serum irisin and myostatin levels and COVID-19 severity.MethodsNinety-nine adult patients hospitalized with PCR-confirmed COVID-19 were included. Serum irisin and myostatin concentrations were measured by ELISA at admission and discharge. Disease severity was evaluated using a four-point clinical scale, the RALE score for lung involvement, oxygenation indices (PaO2/FiO2 and SaO2/FiO2), and inflammatory markers (MMP-9, ferritin, S100B, CRP, D-dimers, NLR, PLR, and SII). ResultsHigher irisin concentrations at admission were associated with more severe clinical condition, increased systemic inflammation, impaired oxygenation, and greater lung involvement. Elevated irisin levels were linked to an increased risk of progression to critical illness, although they were not independent predictors. During hospitalization, irisin levels declined in most patients, in parallel with clinical improvement and reductions in inflammatory markers. Myostatin concentrations at admission correlated with ferritin and D-dimer levels. Higher myostatin levels were associated with severe disease and poorer oxygenation at discharge. Myostatin concentrations remained stable in most patients. Those with declining levels had higher inflammatory markers at baseline but did not differ clinically from others. DiscussionThese findings suggest that, through the release of bioactive myokines, skeletal muscles contribute to the regulation of systemic inflammation and oxygenation, thereby influencing the clinical course of SARSCoV-2 infection. Elevated irisin reflects heightened inflammation, severe hypoxemia, and extensive lung involvement, whereas increased myostatin is associated with severe inflammation and critical illness.